Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Production of functional human nerve growth factor from the submandibular glands of mice using a CRISPR/Cas9 genome editing system - Yi Gu; Hui Cao; Fei Li; Jianli Yu; Rui Nian; Dongxiao Feng; Jingtao Lin; Haipeng Song; Wenshuai Liu (World Journal of Microbiology and Biotechnology, 2020)

Pore-Scale Water Vapor Condensation Behaviors in Shales: An Experimental Study - Guijie Sang; Shimin Liu; Derek Elsworth; Rui Zhang; Markus Bleuel (Transport in Porous Media, 2020)

Busulfan Suppresses Autophagy in Mouse Spermatogonial Progenitor Cells via mTOR of AKT and p53 Signaling Pathways - Rui Wei; Xiaoyu Zhang; Yihui Cai; Hongyang Liu; Bingyuan Wang; Xiaodong Zhao; Kang Zou (Stem Cell Reviews and Reports, 2020)

A Comprehensive Experimental Study on Mechanical Behavior, Microstructure and Transport Properties of 3D-printed Rock Analogs - Rui Song; Yao Wang; Sergey Ishutov; Gonzalo Zambrano-Narvaez; Kevin J. Hodder; Rick J. Chalaturnyk; Shuyu Sun; Jianjun Liu; Ranjith P. Gamage (Rock Mechanics and Rock Engineering, 2020)

Neonatal curcumin treatment restores hippocampal neurogenesis and improves autism-related behaviors in a mouse model of autism - Hongyu Zhong; Rui Xiao; Ruotong Ruan; Hui Liu; Xin Li; Yun Cai; Jinghui Zhao; Xiaotang Fan (Psychopharmacology, 2020)

Farrerol maintains the contractile phenotype of VSMCs via inactivating the extracellular signal-regulated protein kinase 1/2 and p38 mitogen-activated protein kinase signaling - Enli Liu; Shasha Shi; Jie Li; Rui Ge; Taigang Liang; Qingshan Li (Molecular and Cellular Biochemistry, 2020)

Elevated plasma phage load as a marker for intestinal permeability in leukemic patients - Xue-rui Yin; Ping Liu; Xi Xu; Ying Xia; Kai-zhao Huang; Qiong-dan Wang; Mei-mei Lai; Qi-gui Yu; Xiao-qun Zheng (Medical Microbiology and Immunology, 2020)

A review of the Chinese monotypic genus Melliodendron (Styracaceae), with a new synonym of M. xylocarpum - Xue-Hui Wu; Rui Zhang; Timothy M. A. Utteridge; Yu-Lin Liu; Guang-Yao Yang; Ming Tang (Kew Bulletin, 2020)

Reducible Fraction Dominates the Mobility of Vanadium in Soil Around an Iron Smelter - Long Zhijie; Huang Yi; Zhang Wei; Shi Zhangliang; Yu Daming; Chen Yin; Liu Chao; Wang Rui (Bulletin of Environmental Contamination and Toxicology, 2020)

Fundamental Characteristics of Tropical Rain Cell Structures as Measured by TRMM PR - Yunfei Fu; Yilun Chen; Xiangdong Zhang; Yu Wang; Rui Li; Qi Liu; Lei Zhong; Qiong Zhang; Aoqi Zhang (Journal of Meteorological Research, 2020)

MHC-DRB1 exon 2 polymorphism and its association with mycoplasma ovipneumonia resistance or susceptibility genotypes in sheep - Kaisheng Wang; Xianxia Liu; Qiongqiong Li; Kexing Wan; Rui Gao; Guohua Han; Chaochen Li; Mengsi Xu; Bin Jia; Xiaoyun Shen (Journal of Genetics, 2020)

Comparison of rapid freezing versus vitrification for human sperm cryopreservation using sucrose in closed straw systems - Huanhuan Hu; Guojie Ji; Xiaowei Shi; Rui Liu; Jing Zhang; Han Zhang; Xiaozheng Yuan; Guoyi Zhang; Wenzheng Yuan; Mingwen Li (Cell and Tissue Banking, 2020)

Sphingobacterium endophyticum sp. nov., a novel endophyte isolated from halophyte - Yang-Yang Liu; Fang Liu; Yu-Qian Li; Rui-Feng Lei; Qin Ma; Manik Prabhu Narsing Rao; Dilireba Abudourousuli; Zulihumaer Rouzi; Muyesaier Aosiman; Deng-Di An; Wen-Jun Li (Archives of Microbiology, 2020)

Light grazing facilitates carbon accumulation in subsoil in Chinese grasslands: A meta‐analysis - Zhi‐Yun Jiang; Zhong‐Min Hu; Derrick Y. F. Lai; Dao‐Rui Han; Mei Wang; Min Liu; Meng Zhang; Ming‐Yan Guo (Global Change Biology, 2020)
Grazing by livestock greatly affects the soil carbon (C) cycle in grassland ecosystems. However, the effects of grazing at different intensities and durations on the dynamics of soil C in its subsoil layers are not clearly understood. Here, we compiled data from 78 sites (in total 122 published studies) to examine the effects of varying grazing intensities and durations on soil C content at different depths for grasslands in China. Our meta‐analysis revealed that grazing led to an overall decrease in soil C content and productivity of above‐ground vegetation (e.g., above‐ground biomass and litter) but an increase in below‐ground biomass. Specifically, the effects of grazing on soil C content became less negative or even positive with increasing soil depths. An increase of soil C content was consequently found under light grazing (LG), although soil C content still decreased under moderate and heavy grazing. The increase in soil C content under LG could be largely attributed to the increase of soil C content in subsoil layers (>20 cm), despite that soil C content in surface soil layer (0–20 cm) decreased. Moreover, the magnitude of increase in soil C content under LG in subsoil layers increased with grazing duration. A possible reason of the increase in soil C content in the subsoil layers was due to the increases in below‐ground biomass. Our study highlights that LG may modify the allocation of C input and promote its accumulation in subsoil layers, thus offsetting the negative impact of grazing on surface soil C content, a finding that has significant implications for C sequestration in grasslands.

Hybrid Partition-Based Patrolling Scheme for Maritime Area Patrol with Multiple Cooperative Unmanned Surface Vehicles - Jiajia Xie; Rui Zhou; Jun Luo; Yan Peng; Yuan Liu; Shaorong Xie; Huayan Pu (Journal of Marine Science and Engineering, 2020)
Multi-robot cooperative patrolling systems have been extensively employed in the civilian and military fields, including monitoring forest fires, marine search-and-rescue, and area patrol. Multi-robot area patrol problems refer to the activity that a team of robots works cooperatively and regularly to visit the key targets in the given area for security. Following consideration of the low cost and high safety of unmanned surface vehicles (USV), a team of USVs is organized to perform area patrol in a sophisticated maritime environment. In this paper, we establish a mathematical model considering the characteristics of the cooperative patrol task and the limited conditions of USVs. A hybrid partition-based patrolling scheme is proposed for a multi-USV system to visit targets with different importance levels in a maritime area. Firstly, a centralized area partition algorithm is utilized to partition the patrolling area according to the number of USVs. Secondly, a distributed path planning algorithm is applied to planning the patrolling path for each USV to visit the targets in a maritime environment to minimize the length of the patrolling path for the USV team. Finally, comparative experiments between the proposed scheme and other methods are carried out to validate the performance of the hybrid partition-based patrolling scheme. Simulation results and experimental analysis show the efficiency of the proposed hybrid partition-based patrolling scheme compared to several previous patrolling algorithms.

Energy conservation and carbon reduction potential for solid waste in China - Minxi Wang; Zhi Li; Lu Chen; Ping Liu; Rui Zhang; Wei Liu; Yu Ma; Yajie Wang; Xin Li (Environmental Science and Pollution Research, 2020)

The Forms, Distribution, and Risk Assessment of Sulfonamide Antibiotics in the Manure–Soil–Vegetable System of Feedlot Livestock - Caixia Jin; Shan Wei; Ruilian Sun; Wei Zou; Xingli Zhang; Qixing Zhou; Rui Liu; Liuqun Huang (Bulletin of Environmental Contamination and Toxicology, 2020)

Utilizing borehole electrical image and conventional logs to characterize petrology of mixed volcanic and sedimentary rocks in Jiamuhe Formation at JL2 Wellfield, Zhongguai Uplift, Junggar Basin, NW China - Rui Yuan; Lei Zhang; Qinghai Xu; Youlun Feng; Zhiyuan An; Jun Wu; Kang Zhao; Shuai Liu; Peng Huang (Arabian Journal of Geosciences, 2020)

Surface display system for probiotics and its application in aquaculture - Yuan‐Yuan Yao; Ya‐Lin Yang; Chen‐Chen Gao; Feng‐Li Zhang; Rui Xia; Dong Li; Juan Hu; Chao Ran; Zhen Zhang; Jihong Liu‐Clarke; Zhi‐Gang Zhou (Reviews in Aquaculture, 2020)
Aquaculture is a fast‐growing and rapidly expanding industry in the world. Probiotics are widely used in aquaculture and have provided benefits to aquatic animal health, and it is also a promising alternative to antibiotics for control of fish diseases. With the development of biotechnology, new expression systems and novel techniques for the surface display of heterologous proteins in surface of probiotics cells have been developed. This review provides an overview of the systems and strategies for displaying functional proteins on the surface of probiotics commonly used in aquaculture, which are Bacillus subtilis , Bacillus thuringiensis , lactic acid bacteria represented by Lactococcus lactis and yeast. Their applications in aquaculture especially for oral vaccine development afforded by this technology and prospects and challenges associated with this technology are also highlighted.

Multi-AUVs Cooperative Target Search Based on Autonomous Cooperative Search Learning Algorithm - Yuan Liu; Min Wang; Zhou Su; Jun Luo; Shaorong Xie; Yan Peng; Huayan Pu; Jiajia Xie; Rui Zhou (Journal of Marine Science and Engineering, 2020)
As a new type of marine unmanned intelligent equipment, autonomous underwater vehicle (AUV) has been widely used in the field of ocean observation, maritime rescue, mine countermeasures, intelligence reconnaissance, etc. Especially in the underwater search mission, the technical advantages of AUV are particularly obvious. However, limited operational capability and sophisticated mission environments are also difficulties faced by AUV. To make better use of AUV in the search mission, we establish the DMACSS (distributed multi-AUVs collaborative search system) and propose the ACSLA (autonomous collaborative search learning algorithm) integrated into the DMACSS. Compared with the previous system, DMACSS adopts a distributed control structure to improve the system robustness and combines an information fusion mechanism and a time stamp mechanism, making each AUV in the system able to exchange and fuse information during the mission. ACSLA is an adaptive learning algorithm trained by the RL (Reinforcement learning) method with a tailored design of state information, reward function, and training framework, which can give the system optimal search path in real-time according to the environment. We test DMACSS and ACSLA in the simulation test. The test results demonstrate that the DMACSS runs stably, the search accuracy and efficiency of ACSLA outperform other search methods, thus better realizing the cooperation between AUVs, making the DMACSS find the target more accurately and faster.

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Tree-ring-based temperature reconstruction since 1766 ce in the eastern Tianshan Mountains, arid Central Asia - Zhengbing Peng; Li Qin; Xinjian Li; Heli Zhang; Youping Chen; Rui Liu; Ruibo Zhang (Theoretical and Applied Climatology, 2020)

New Value-Added Sugar and Brown Sugar Products from Sugarcane: A Commercial Approach - Liu Yang; Shi-Yan Shen; Zhi-Neng Wang; Ting Yang; Jia-Wen Guo; Rui-Yun Hu; Yan-Fang Li; David M. Burner; Xiong-Mei Ying (Sugar Tech, 2020)

High expression of long non-coding RNA Linc-A associates with poor survival in patients with colorectal cancer - Chong Zhao; Can Gan; Yang Xiao; Rui Liu; Linhao Zhang; Tian Lan; Yanting Ye; Huan Tong; Zhiyin Huang; Chengwei Tang; Jinhang Gao (Molecular Biology Reports, 2020)

Down-regulation of SETD6 protects podocyte against high glucose and palmitic acid-induced apoptosis, and mitochondrial dysfunction via activating Nrf2-Keap1 signaling pathway in diabetic nephropathy - Xiang Wang; Qiling Liu; Deqin Kong; Zi Long; YuFang Guo; Shuang Wang; Rui Liu; Chunxu Hai (Journal of Molecular Histology, 2020)

Ultrafiltration and microfiltration membrane performance, cleaning, and flux recovery for microalgal harvesting - Rui Liu; Lan Wang; Li Yang; Qingling Liu; Yunxiao Gao; Jing Ye; Jingrong Xiao; Qiang Hu; Xuezhi Zhang (Journal of Applied Phycology, 2020)

Fluoride Inhibits Longitudinal Bone Growth by Acting Directly at the Growth Plate in Cultured Neonatal Rat Metatarsal Bones - Rui Ma; Shuang Liu; Tingting Qiao; Demin Li; Ruixue Zhang; Xiaoying Guo (Biological Trace Element Research, 2020)

Can a low-carbon development path achieve win-win development: evidence from China’s low-carbon pilot policy - Cenjie Liu; Zhongbao Zhou; Qing Liu; Rui Xie; Ximei Zeng (Mitigation and Adaptation Strategies for Global Change, 2020)

Evaluating Spatial Heterogeneity of Land Surface Hydrothermal Conditions in the Heihe River Basin - Yuan Zhang; Shaomin Liu; Xiao Hu; Jianghao Wang; Xiang Li; Ziwei Xu; Yanfei Ma; Rui Liu; Tongren Xu; Xiaofan Yang (Chinese Geographical Science, 2020)

MELK Accelerates the Progression of Colorectal Cancer via Activating the FAK/Src Pathway - Guangming Liu; Wei Zhan; Wei Guo; Feng Hu; Junjie Qin; Rui Li; Xin Liao (Biochemical Genetics, 2020)

Formation of nano- or near-nanoparticles via oxidation in the Dabaoshan concealed deposit, Guangdong Province - Rui Liu; Jianjin Cao; Yongkang Deng; Guoqiang Wang; Xiang Liu (Arabian Journal of Geosciences, 2020)

What maintains seasonal nitrogen limitation in hyper-eutrophic Lake Dianchi? Insights from stoichiometric three-dimensional numerical modeling - Zhen Wu; Rui Zou; Qingsong Jiang; James J. Elser; Lei Zhao; Rui Ye; Yong Liu (Aquatic Sciences, 2020)

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

The cyclic lipopeptides suppress the motility of Vibrio alginolyticus via targeting the Na + ‐driven flagellar motor component MotX - Rui Liu; Rikuan Zheng; Ge Liu; Chaomin Sun (Environmental Microbiology, 2020)
Summary In our previous study, we found that pumilacidin‐like cyclic lipopeptides (CLPs) derived from marine bacterium Bacillus sp. strain 176 significantly suppressed the mobile capability and virulence of Vibrio alginolyticus . Here, to further disclose the mechanism of CLPs inhibiting the motility of V . alginolyticus , we first applied transcriptomic analysis to V . alginolyticus treated with or without CLPs. The transcriptomic results showed that the expression of several important components of the Na + ‐driven flagellar motor closely related to bacterial motility were markedly suppressed, suggesting that the structure and function of Na + ‐driven flagellar motor might be disabled by CLPs. The transcriptomic data were further analysed by the protein–protein interaction network, and the results supported that MotX, one of the essential components of Na + ‐driven flagellar motor was most likely the action target of CLPs. In combination of gene knockout, electrophoretic mobility shift assay and immunoblotting techniques, CLPs were demonstrated to affect the rotation of flagella of Vibrio alginolyticus via direct interacting with the Na + ‐driven flagellar motor component MotX, which eventually inhibited the bacterial motility. Interestingly, homologues of MotX were found broadly distributed and highly conserved in different pathogenic species, which extends the application range of CLPs as an antibacterial drug targeting bacterial motility in many pathogens.

The abscisic acid receptor gene VvPYL4 positively regulates grapevine resistance to Plasmopara viticola - Li Liu; Chang-Yuan Liu; Hui Wang; Shu-Yi Yu; Tian-Shu Guan; Yu-Fei Huang; Rui-Chun Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Apigetrin ameliorates streptozotocin-induced pancreatic β-cell damages via attenuating endoplasmic reticulum stress - Rui Zhang; Jie Shi; Tingting Wang; Xiaonan Qiu; Ruixia Liu; Yitian Li; Qing Gao; Ning Wang (In Vitro Cellular & Developmental Biology - Animal, 2020)

Isolation and functional characterization of the mitogen-activated protein kinase kinase gene MAPKK1 from Panax notoginseng - Limei Pu; Rui Chen; Shah Taif; Qin Zhao; Xin Li; Yuan Qu; Xiuming Cui; Diqiu Liu (European Journal of Plant Pathology, 2020)

The direct and indirect effects of democracy on carbon dioxide emissions in BRICS countries: evidence from panel quantile regression - Yinghua Ren; Lisi Liu; Huiming Zhu; Rui Tang (Environmental Science and Pollution Research, 2020)

Mechanical characteristics of soil-rock mixtures containing macropore structure based on 3D modeling technology - Yong Liu; Shao-rui Sun; Ji-hong Wei; Jing-lei Song; Yong-xiang Yu; Wei He; Ji-xing Zhang (Journal of Mountain Science, 2020)

Low-frequency swell noise suppression based on U-Net - Rui-qi Zhang; Peng Song; Bao-hua Liu; Xiao-bo Zhang; Jun Tan; Zhi-hui Zou; Chuang Xie; Shao-wen Wang (Applied Geophysics, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Reductions in water, soil and nutrient losses and pesticide pollution in agroforestry practices: a review of evidence and processes - Xiai Zhu; Wenjie Liu; Jin Chen; L. Adrian Bruijnzeel; Zhun Mao; Xiaodong Yang; Rémi Cardinael; Fan-Rui Meng; Roy C. Sidle; Steffen Seitz; Vimala D. Nair; Kazuki Nanko; et al. (Plant and Soil, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

Pseudomonas Saliphila sp. nov., a Bacterium Isolated from Oil-Well Production Water in Qinghai Oilfield of China - Xiao-Juan Zhang; Hong-Can Liu; Yu-Guang Zhou; Xiao-Lei Wu; Yong Nie; Qi-Rui Li; Mei-Zhu Wang; Liang Zhao; Man Cai; Ying-Qian Kang (Current Microbiology, 2020)

Isolation and Identification of Endophytic Fungi in Kernels of Coix lachrymal-jobi L. Cultivars - Guan-rong Li; Bao-hong Cao; Wei Liu; Rui-hua Ren; Jie Feng; Da-jin Lv (Current Microbiology, 2020)

The Environmental Functions and Ecological Effects of Organic Carbon in Silt - Rui Liu; Teng Ma; Wenkai Qiu; Ziqi Peng; Chenxuan Shi (Journal of Earth Science, 2020)

Critical transition of soil bacterial diversity and composition triggered by nitrogen enrichment - Weixing Liu; Lin Jiang; Sen Yang; Zhou Wang; Rui Tian; Ziyang Peng; Yongliang Chen; Xingxu Zhang; Jialiang Kuang; Ning Ling; Shaopeng Wang; Lingli Liu (Ecology, 2020)
Soil bacterial communities are pivotal in regulating terrestrial biogeochemical cycles and ecosystem functions. The increase in global nitrogen (N) deposition has impacted various aspects of terrestrial ecosystems, but we still have a rudimentary understanding of whether there is a threshold for N input level beyond which soil bacterial communities will experience critical transitions. Using high‐throughput sequencing of the 16S rRNA gene, we examined soil bacterial responses to a long‐term (13 yr), multi‐level, N addition experiment in a temperate steppe of northern China. We found that plant diversity decreased in a linear fashion with increasing N addition. However, bacterial diversity responded nonlinearly to N addition, such that it was unaffected by N input below 16 g N·m −2 ·yr −1 , but decreased substantially when N input exceeded 32 g N·m −2 ·yr −1 . A meta‐analysis across four N addition experiments in the same study region further confirmed this nonlinear response of bacterial diversity to N inputs. Substantial changes in soil bacterial community structure also occurred between N input levels of 16 to 32 g N·m −2 ·yr −1 . Further analysis revealed that the loss of soil bacterial diversity was primarily attributed to the reduction in soil pH, whereas changes in soil bacterial community were driven by the combination of increased N availability, reduced soil pH, and changes in plant community structure. In addition, we found that N addition shifted bacterial communities toward more putatively copiotrophic taxa. Overall, our study identified a threshold of N input level for bacterial diversity and community composition. The nonlinear response of bacterial diversity to N input observed in our study indicates that although bacterial communities are resistant to low levels of N input, further increase in N input could trigger a critical transition, shifting bacterial communities to a low‐diversity state.

Reconstruction of nearshore chemical conditions in the Mesoproterozoic: evidence from red and grey beds of the Yangzhuang formation, North China Craton - Yu Zou; Dongna Liu; Fenghua Zhao; Hongwei Kuang; Changgui Song; Yuxiang Sun; Rui Zhou; Jianbo Cheng (International Geology Review, 2020)

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

Gradation affects basic mechanical characteristics of Chinese calcareous sand as airport subgrade of reefs - Shen Yang; Xue Shen; Hanlong Liu; Huayang Ge; Xiaoxi Rui (Marine Georesources & Geotechnology, 2020)

Examining two sets of introgression lines across multiple environments reveals background-independent and stably expressed quantitative trait loci of fiber quality in cotton - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Shaoqi Li; Jinfeng Zhang; Liujun Ma; Rui He; Weiwu Song; Lixue Guo; Quanwei Lu; Xianghui Xiang; et al. (Theoretical and Applied Genetics, 2020)
Key message Background-independent (BI) and stably expressed (SE) quantitative trait loci (QTLs) were identified using two sets of introgression lines across multiple environments. Genetic background more greatly affected fiber quality traits than environmental factors. Sixty-one SE-QTLs, including two BI-QTLs, were novel and 48 SE-QTLs, including seven BI-QTLs, were previously reported. Abstract Cotton fiber quality traits are controlled by QTLs and are susceptible to environmental influence. Fiber quality improvement is an essential goal in cotton breeding but is hindered by limited knowledge of the genetic basis of fiber quality traits. In this study, two sets of introgression lines of Gossypium hirsutum × G. barbadense were used to dissect the QTL stability of three fiber quality traits (fiber length, strength and micronaire) across environments using 551 simple sequence repeat markers selected from our high-density genetic map. A total of 76 and 120 QTLs were detected in the CCRI36 and CCRI45 backgrounds, respectively. Nine BI-QTLs were found, and 78 (41.71%) of the detected QTLs were reported previously. Thirty-nine and 79 QTLs were SE-QTLs in at least two environments in the CCRI36 and CCRI45 backgrounds, respectively. Forty-eight SE-QTLs, including seven BI-QTLs, were confirmed in previous reports, and 61 SE-QTLs, including two BI-QTLs, were considered novel. These results indicate that genetic background more strongly impacts on fiber quality traits than environmental factors. Twenty-three clusters with BI- and/or SE-QTLs were identified, 19 of which harbored favorable alleles from G. barbadense for two or three fiber quality traits. This study is the first report using two sets of introgression lines to identify fiber quality QTLs across environments in cotton, providing insights into the effect of genetic backgrounds and environments on the QTL expression of fiber quality and important information for the genetic basis underlying fiber quality traits toward QTL cloning and molecular breeding.

The role of miRNA-155 in monocrotaline-induced pulmonary arterial hypertension through c-Fos/NLRP3/caspase-1 - Shou-Dong Chai; Zhen-Kun Li; Rui Liu; Tao Liu; Ming-Feng Dong; Pei-Zhe Tang; Jian-Tang Wang; Sheng-Jun Ma (Molecular & Cellular Toxicology, 2020)

Visible and near-infrared spectroscopy with chemometrics are able to predict soil physical and chemical properties - Jinbao Liu; Jiancang Xie; Jichang Han; Huanyuan Wang; Jianhong Sun; Rui Li; Shaoxuan Li (Journal of Soils and Sediments, 2020)

SNHG16 regulates invasion and migration of bladder cancer through induction of epithelial-to-mesenchymal transition - Wenwei Chen; Tao Jiang; Houping Mao; Rui Gao; Hua Zhang; Yanfeng He; Changyi Liu; Qin Chen (Human Cell, 2020)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

Dryness/wetness pattern over the Three‐River Headwater Region: Variation characteristic, causes, and drought risks - Sisi Li; Zhijun Yao; Rui Wang; Zhaofei Liu (International Journal of Climatology, 2020)
The dryness/wetness patterns are a significant reference for stakeholders in developing reasonable strategies in regard to water resource management, prediction, prevention of extreme events, and management of agricultural activities; however, no attempts have been made to systematically quantify the dryness/wetness patterns and drought conditions over the Three‐River Headwater Region (TRHR) of China, where the ecosystem is highly sensitive to climate change. The spatio‐temporal characteristics of dryness/wetness for TRHR, as well as the reference evapotranspiration (ETr), precipitation (Pre), and drought risk, were all investigated for the period of 1961–2015. Using the methods of FAO‐56 Penman–Monteith (FAO‐56), standardized precipitation evapotranspiration index (SPEI), the Manner–Kendall (M–K) test, Pettitt test, factor contribution rate, and correlation analysis, the variation in the patterns of dryness/wetness, ETr, and Pre, and the causes behind dryness/wetness were discussed. Results indicated that the TRHR underwent a wetting tendency, which was characterized by decreasing ETr and increasing Pre based on the SPEI‐12M during 1961–2015. Moreover, 1971–1980 was the driest period, while 2001–2015 was the wettest period. A significant difference between seasons was detected in the dryness/wetness patterns during all study periods, as well as in extreme droughts. The TRHR underwent an overall wetting trend with 85% of the stations' SPEI‐3M showing increased variation during spring, in contrast with the north–south distribution pattern of the dryness/wetness with variation in the SPEI during summer. Moreover, it can be seen that droughts with higher longest drought duration (LDD) and total drought duration (TDD) were mostly located on the edge of the eastern and northern TRHR. The influencing factors demonstrate the vital roles of Pre and ETr in generating variation in the dryness/wetness patterns of the southern and northern parts of the TRHR, respectively. There is evidence indicating that Niño3.4, North Atlantic oscillation, and Arctic oscillation played more important roles in the variation of dryness/wetness patterns and Pre in TRHR.

Salvianolic acid A attenuated myocardial infarction–induced apoptosis and inflammation by activating Trx - Rui Zhou; Jinhuan Gao; Changpei Xiang; Zhenming Liu; Yi Zhang; Jingjing Zhang; Hongjun Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

The Role of 17β-Estrogen in Candida albicans Adhesion on Human Vaginal Epithelial Cells via FAK Phosphorylation - Ting Luan; Xia Liu; Pengyuan Mao; Xinyan Wang; Can Rui; Lina Yan; Yiquan Wang; Chong Fan; Ping Li; Xin Zeng (Mycopathologia, 2020)

Field survey of a catastrophic high-speed long-runout landslide in Jichang Town, Shuicheng County, Guizhou, China, on July 23, 2019 - Weihua Zhao; Rui Wang; Xiuwei Liu; Nengpan Ju; Mingli Xie (Landslides, 2020)

Characterization of a Rapeseed Anthocyanin-More Mutant with Enhanced Resistance to Sclerotinia sclerotiorum - Rui Liu; Li-Na Ding; Ming Li; Wei Cao; Yu-Kang Wang; Wei-Jie Wang; Yan-Kun Yu; Zheng Wang; Ke-Ming Zhu; Xiao-Li Tan (Journal of Plant Growth Regulation, 2020)

Effects of different NO3−:NH4+ ratios on the photosynthesis and ultrastructure of lettuce seedlings - Xu Zhu; Rui Yang; Yingyan Han; Jinghong Hao; Chaojie Liu; Shuangxi Fan (Horticulture, Environment, and Biotechnology, 2020)

Assessment of genetic diversity in Camellia oleifera Abel. accessions using inter-simple sequence repeat (ISSR) and start codon targeted (SCoT) polymorphic markers - Pu Xiao; Huhu Liu; Dongping Wang; Wenyan Tang; Hui Yang; Chong Wang; Zhilong He; Rui Wang; Xiangnan Wang; Xiangyang Lu; Yongzhong Chen; Yun Tian (Genetic Resources and Crop Evolution, 2020)

Quality dependence of litter decomposition and its carbon, nitrogen and phosphorus release under simulated acid rain treatments - Hui Wei; Rui Ma; Jiaen Zhang; Leyi Zhou; Ziqiang Liu; Zhenyi Fan; Jiayue Yang; Xiaoran Shan; Huimin Xiang (Environmental Science and Pollution Research, 2020)

Structural Networks Constraints on Alteration and Mineralization Processes in the Jiaojia Gold Deposit, Jiaodong Peninsula, China - Huanlong Hu; Shuangliang Liu; Hong-Rui Fan; Kuifeng Yang; Yabin Zuo; Yachun Cai (Journal of Earth Science, 2020)

Lactate accelerates vascular calcification through NR4A1-regulated mitochondrial fission and BNIP3-related mitophagy - Yi Zhu; Xi-Qiong Han; Xue-Jiao Sun; Rui Yang; Wen-Qi Ma; Nai-Feng Liu (Apoptosis, 2020)

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

PDB-1 from Potentilla discolor Bunge suppresses lung cancer cell migration and invasion via FAK/Src and MAPK signaling pathways - Na-na Meng; Rui-rui Zhang; Chao Liu; Qing Wang; Xin-kun Wang; Xu Guo; Ping-ping Wang; Jin-yue Sun (Medicinal Chemistry Research, 2020)

Spent mushroom substrate combined with alkaline amendment passivates cadmium and improves soil property - Zonghui Jin; Meng Zhang; Rui Li; Xu Zhang; Guoliang Wang; Xuesheng Liu; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

Natural HgS nanoparticles in sulfide minerals from the Hetai goldfield - Xiang Liu; Rui Liu; Genwen Chen; Xiaoen Luo; Meiqu Lu (Environmental Chemistry Letters, 2020)

Paracetamol affects the expression of detoxification- and reproduction-related genes and alters the life traits of Daphnia magna - Rui Ding; Sijia Liu; Cuiping He; Xiangping Nie (Ecotoxicology, 2020)

Characteristics and dynamics of the Ganqiuchi rock avalanche triggered by a paleo-earthquake in the Northern Qinling Mountains - Ze-Hua Zhou; Yan Lyu; Sheng-rui Su; Shi-jie Liu; Hui Zhao; Peng Li; Yang Zhou (Journal of Mountain Science, 2020)

New cytotoxic bufadienolides from the roots and rhizomes of Helleborus thibetanus Franch - Yuze Li; Huawei Zhang; Xiaofei Liang; Bei Song; Xudong Zheng; Rui Wang; Li Liu; Xiaomei Song; Jianli Liu (Natural Product Research, 2020)

Mouse adaptation of the H9N2 avian influenza virus causes the downregulation of genes related to innate immune responses and ubiquitin-mediated proteolysis in mice - Jing Guo; Xinxin Gao; Baotao Liu; Yubao Li; Wenqiang Liu; Jianbiao Lu; Cheng Liu; Rui Xue; Xuyong Li (Medical Microbiology and Immunology, 2020)

Long-term fertilization and intensive cropping enhance carbon and nitrogen accumulated in soil clay-sized particles of red soil in South China - Hu Xu; Kailou Liu; Wenju Zhang; Yichao Rui; Jingye Zhang; Lei Wu; Gilles Colinet; Qinghai Huang; Xianni Chen; Minggang Xu (Journal of Soils and Sediments, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Improve uridine production by modifying related metabolic pathways in Bacillus subtilis - Xueting Zhang; Chen Wang; Lu Liu; Rui Ban (Biotechnology Letters, 2020)

Isolation of a novel strain Aspergillus niger WH-2 for production of l(+)-tartaric acid under acidic condition - Wenna Bao; Hongxiu Liao; Yi Chen; Qianqian Huang; Wendi Huang; Rui Fang; Shiwang Liu (Biotechnology Letters, 2020)

Stable Isotope Evidence for Recent Global Warming Hiatus - Rui Wang; Zhongfang Liu (Journal of Earth Science, 2020)

LIN9 confers paclitaxel resistance in triple negative breast cancer cells by upregulating CCSAP - Hongna Lai; Rui Wang; Shunying Li; Qianfeng Shi; Zijie Cai; Yudong Li; Yujie Liu (Science China Life Sciences, 2020)

miR477 targets the phenylalanine ammonia-lyase gene and enhances the susceptibility of the tea plant (Camellia sinensis) to disease during Pseudopestalotiopsis species infection - Shuangshuang Wang; Shengrui Liu; Lu Liu; Rui Li; Rui Guo; Xiaobo Xia; Chaoling Wei (Planta, 2020)

Bibliometric analysis of research on soil health from 1999 to 2018 - Yanan Liu; Kening Wu; Rui Zhao (Journal of Soils and Sediments, 2020)

Effect of carbon rate and type amended with ammonium or nitrate on nitrous oxide emissions in a strong ammonia oxidation soil - Liuqing Yang; Rui Liu; Xiaotang Ju (Journal of Soils and Sediments, 2020)

Heritability of resistance-related gene expression traits and their correlation with body size of clam Meretrix petechialis - Fengjuan Jiang; Xin Yue; Shujing Zhang; Jiajia Yu; Rui Wang; Baozhong Liu; Hongxia Wang (Journal of Oceanology and Limnology, 2020)

Effects of florfenicol exposure on growth, development and antioxidant capacity of flounder Paralichthys olivaceus larvae at different developmental stages - Rui Guo; Yingqi Zhang; Xianyu Zhang; Qian Zhang; Rui Cheng; Rahman Md Mostafizur; Ying Liu (Journal of Oceanology and Limnology, 2020)

The stability and pressure behavior characteristics of a special L-type face end formed by low-pressure mining technology without pre-driving roadway - Ya-jun Wang; Jun Yang; Man-chao He; Rui-feng Huang; Xi-chun Tian; Jian-ning Liu; Hao-jie Xue (Arabian Journal of Geosciences, 2020)

Simulation of T-bar penetration in soft clay with adhesive contact - Teng Wang; Rui Wu; Wenlong Liu; Xingxian Bao (Marine Georesources & Geotechnology, 2020)

Aromatic compounds from Endocomia macrocoma - Fang Kuang; Ying Liu; Ye-Gao Chen; Rui Zhan (Natural Product Research, 2020)

Age- and region-related response of radial growth to climate warming and a warming hiatus - Lingnan Zhang; Rui Wang; Xianfeng Liu; Yilin Ran; Shu Shang; Xiaohong Liu (Trees, 2020)

Differential anthocyanin accumulation in radish taproot: importance of RsMYB1 gene structure - Biao Lai; Yuanyi Cheng; Hong Liu; Qiuxia Wang; Qi Wang; Chunlan Wang; Rui Su; Fabo Chen; Huicong Wang; Lina Du (Plant Cell Reports, 2020)

Allelopathy confers an invasive Wedelia higher resistance to generalist herbivore and pathogen enemies over its native congener - Shan-Shan Qi; Yan-Jie Liu; Zhi-Cong Dai; Ling-Yun Wan; Dao-Lin Du; Rui-Ting Ju; Justin S. H. Wan; Stephen P. Bonser (Oecologia, 2020)

MiR-125a-5p Regulates Vitamin D Receptor Expression in a Mouse Model of Experimental Autoimmune Encephalomyelitis - Han-Chun Long; Rui Wu; Chun-Feng Liu; Fei-Long Xiong; Zu Xu; Dian He; Yi-Fan Zhang; Bing Shao; Ping-An Zhang; Guang-Yin Xu; Lan Chu (Neuroscience Bulletin, 2020)

Remobilization of metasomatized mantle lithosphere: a new model for the Jiaodong gold province, eastern China - Jun Deng; Qingfei Wang; M Santosh; Xuefei Liu; Yayun Liang; Liqiang Yang; Rui Zhao; Lin Yang (Mineralium Deposita, 2020)

Geochronological and sulfur isotopic evidence for the genesis of the post-magmatic, deeply sourced, and anomalously gold-rich Daliuhang orogenic deposit, Jiaodong, China - Kai Feng; Hong-Rui Fan; David I. Groves; Kui-Feng Yang; Fang-Fang Hu; Xuan Liu; Ya-Chun Cai (Mineralium Deposita, 2020)

Object-Based Mapping of Plastic Greenhouses with Scattered Distribution in Complex Land Cover Using Landsat 8 OLI Images: A Case Study in Xuzhou, China - Li Ji; Lianpeng Zhang; Yang Shen; Xing Li; Wei Liu; Qi Chai; Rui Zhang; Dan Chen (Journal of the Indian Society of Remote Sensing, 2020)

Response of organic carbon fractions and microbial community composition of soil aggregates to long-term fertilizations in an intensive greenhouse system - Lihong Tong; Ling Zhu; Yizhong Lv; Kun Zhu; Xiayan Liu; Rui Zhao (Journal of Soils and Sediments, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Risk factors and clinical characteristics of tacrolimus-induced acute nephrotoxicity in children with nephrotic syndrome: a retrospective case-control study - Ping Gao; Xin-Lei Guan; Rui Huang; Xiao-Fang Shang-guan; Jiang-Wei Luan; Mao-Chang Liu; Hua Xu; Xiao-Wen Wang (European Journal of Clinical Pharmacology, 2020)

Forest gaps retard carbon and nutrient release from twig litter in alpine forest ecosystems - Bo Tan; Jian Zhang; Wanqin Yang; Rui Yin; Zhenfeng Xu; Yang Liu; Li Zhang; Han Li; Chengming You (European Journal of Forest Research, 2020)

Visualization and analysis of mapping knowledge domain of oxidation studies of sulfide ores - Rui Hong; Hui Liu; Chenglang Xiang; Yimeng Song; Chen Lv (Environmental Science and Pollution Research, 2020)

Mercury exposure in sedentary and migratory Charadrius plovers distributed widely across China - Tongping Su; Xin Lin; Qin Huang; Demeng Jiang; Chi Zhang; Xuecong Zhang; Caroline Dingle; Eben Goodale; Pinjia Que; Rui Wang; Yang Liu (Environmental Science and Pollution Research, 2020)

Impact of Arctic amplification on declining spring dust events in East Asia - Jun Liu; Dongyou Wu; Guangjing Liu; Rui Mao; Siyu Chen; Mingxia Ji; Pingqing Fu; Yele Sun; Xiaole Pan; Hongchun Jin; Yubin Zhou; Xin Wang (Climate Dynamics, 2020)
Dust aerosols play key roles in affecting regional and global climate through their direct, indirect, and semi-direct effects. Dust events have decreased rapidly since the 1980s in East Asia, particularly over northern China, primarily because of changes in meteorological parameters (e.g. surface wind speed and precipitation). In this study, we found that winter (December–January–February) Arctic amplification associated with weakened temperature gradients along with decreased zonal winds is primarily responsible for the large decline in following spring (March–April–May) dust event occurrences over northern China since the mid-1980s. A dust index was developed for northern China by combining the daily frequency of three types of dust event (dust storm, blowing dust, and floating dust). Using the empirical orthogonal function (EOF) analysis, the first pattern of dust events was obtained for spring dust index anomalies, which accounts for 56.2% of the variability during 1961–2014. Moreover, the enhanced Arctic amplification and stronger Northern Hemisphere annular mode (NAM) in winter can result in the anticyclonic anomalies over Siberia and Mongolia, while cyclonic anomalies over East Europe in spring. These results are significantly correlated with the weakened temperature gradients, increased precipitation and soil moisture, and decreased snow cover extent in the mid-latitude over Northern Hemisphere. Based on the future predictions obtained from the Fifth Climate Models Intercomparison Project (CMIP5), we found that the dust event occurrences may continually decrease over northern China due to the enhanced Arctic amplification in future climate.

Quantitative proteomic analysis reveals that the Rap1/MAPK/ERK pathway is inhibited through selenomethionine strengthening antioxidant activity - Zhe Liu; Feng Zhang; Lina Cui; Jihong Wang; Ping Lu; Rui Zhao; Hua Zhang; Jianfa Wang; Chunqiu Li; Rui Wu (BioMetals, 2020)

Crystal structure of impurity-free rhodochrosite (MnCO3) and thermal expansion properties - Wen Liang; Lin Li; Rui Li; Yuan Yin; Zeming Li; Xiqiang Liu; Shuangmin Shan; Yu He; Yong Meng; Zengsheng Li; Heping Li (Physics and Chemistry of Minerals, 2020)

Resonance characteristics of onshore wind turbine tower structure considering the impedance of piled foundations - Lujiong Wang; Rui Zhong; Lin Liu (Arabian Journal of Geosciences, 2020)

Isolation, identification and character analysis of Streptococcus dysgalactiae from Megalobrama terminalis - Fei Zhao; Shan He; Ai‐ping Tan; Xue‐zhong Guo; Lan Jiang; Cui Liu‐Fu; Yu‐ting Deng; Rui‐quan Zhang (Journal of Fish Diseases, 2020)
Pure bacterial cultures were isolated from different tissues of moribund Megalobrama terminalis from a high mortality event that occurred at a farm in Foshan, China. Two isolates (F2 and F3) were identified as Streptococcus dysgalactiae subsp. dysgalactiae based on morphological and biochemical detection as well as molecular analysis. In brain heart infusion broth, the best growth conditions of isolate F3 were 35ºC, salinity 5‰ and pH 7. Furthermore, infection with isolate F3 (1.2 × 10 6 CFU/fish) led to the death of M. terminalis and zebrafish ( Danio rerio ). However, isolate F3 had no obvious pathogenicity to tilapia (GIFT, Oreochromis niloticus ). When the water temperature was 29ºC, the corresponding mortality rates for zebrafish infected by isolate F3 were higher than those at 23ºC. Culture for 24 and 72 hr with isolate F3 resulted in the same mortality rates for zebrafish. The antimicrobial susceptibility assay revealed that isolate F3 was susceptible to ampicillin, florfenicol and several other antibiotics but resistant to nalidixic acid, streptomycin, sulfamethoxazole/trimethoprim, neomycin and amikacin. To our knowledge, this is the first report that S. dysgalactiae infected the subtropical freshwater fish M. terminalis , which indicates that this bacterium is a potential threat to subtropical freshwater fish.

Enhancing remote sensing image retrieval using a triplet deep metric learning network - Rui Cao; Qian Zhang; Jiasong Zhu; Qing Li; Qingquan Li; Bozhi Liu; Guoping Qiu (International Journal of Remote Sensing, 2020)

Hand, foot, and mouth disease in Changsha City, China, 2009–2017: a new method to analyse the epidemiological characteristics of the disease - Dong Yang; Ruchun Liu; Lan Ye; Qingqing Hu; Jia Rui; Yinzhu Zhou; Heng Zhang; Xixing Zhang; Benhua Zhao; Tianmu Chen (Infectious Diseases, 2020)

TNF-α suppresses sweat gland differentiation of MSCs by reducing FTO-mediated m6A-demethylation of Nanog mRNA - Yihui Wang; Rui Wang; Bin Yao; Tian Hu; Zhao Li; Yufan Liu; Xiaoli Cui; Liuhanghang Cheng; Wei Song; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

Stimulation of heterotrophic nitrification and N2O production, inhibition of autotrophic nitrification in soil by adding readily degradable carbon - Ting Lan; Rui Liu; Helen Suter; Ouping Deng; Xuesong Gao; Ling Luo; Shu Yuan; Changquan Wang; Deli Chen (Journal of Soils and Sediments, 2020)

Effects of long-term exposure to air pollution on the incidence of type 2 diabetes mellitus: a meta-analysis of cohort studies - Mei Yang; Han Cheng; Chaowei Shen; Jie Liu; Hongkai Zhang; Jiyu Cao; Rui Ding (Environmental Science and Pollution Research, 2020)

CD271 promotes STZ-induced diabetic wound healing and regulates epidermal stem cell survival in the presence of the pTrkA receptor - Min Zhang; Rui Zhang; Xiaohong Li; Yongqian Cao; Kaifeng Huang; Jun Ding; Mengyao Liu; Zhang Feng; Siyuan Yin; Jiaxu Ma; Huayu Zhang; Yibing Wang (Cell and Tissue Research, 2020)

Genetic variants in circTUBB interacting with smoking can enhance colorectal cancer risk - Ke Zhang; Shuwei Li; Dongying Gu; Kaili Xu; Rui Zheng; Junyi Xin; Yixuan Meng; Shuai Ben; Haiyan Chu; Zhengdong Zhang; Yongqian Shu; Mulong Du; et al. (Archives of Toxicology, 2020)